Environmental Principles and Values in Africa: The Christian Response - Sibani, Cliford Meesua; Chinda, C. Izeoma (NIU Journal of Social Sciences; Vol 10 No 3 (2024): NIU Journal of Social Sciences, Vol. 10 No. 3, September 2024DO - 10.58709/niujss.v10i3.1981, 2024)
This research is focused on Environmental principles and values in Africa: The Christian response. The environment is the habitation of man and all living and non-living things alike. It is being given to man by God to tend and control, however, human activities has greatly impacted it positively and negatively. It is clearer that we live in extraordinary times where human impacts on our environment has been so intensive or so far-reaching negatively. The future of the Earth’s system and our society depend more critically than ever on the way we interact with the natural systems around us. Fundamental conditions in nutrient cycling, biodiversity, atmospheric composition and climate are changing rapidly in Africa.  Understanding the African environment illuminate not only human-induced problem but tremendous opportunities we have before us for effecting positive change. This discipline draws upon the methods and findings of numerous established academic disciplines, from ecology to geology to chemistry to economics to political science to ethics and religion. This interdisciplinary pursuit stands at the vanguard of the current need to synthesize our increasingly narrow academic disciplines and to incorporate their contributions into a big picture of understanding the African world and our place within it. In the light of this paper, various authors have put forth definitions on environment, environmental justice and principles of environmental, environmental values in Africa via Christian response, African environment and sustainable development principle, the church response on environmental values in Africa. This research made used of analytical method as well as the utilisation of books, journals, internet sources etc., and recommends among others that humans should care for the earth with tenderness for its benevolence and to avert disaster. Keywords: Africa, Christian, Environment, Justice, Principles, Values